A Study on Implementation In Education & 74Th Amendment Through Municipal Corporation: a Case Study of Mcd: Examining the impact of the 74th Amendment on education implementation through a case study of MCD (Journal of Advances and Scholarly Researches in Allied Education, 2015)
There exist manyactors within the realm of education policy planning and implementation,namely: the policy makers; the national, local and regional institutionsengaged in the dissemination and interpretation of these policies; and theeducational institutions that implement these policies at the ground level(schools). While schools are largely perceived to be at the receiving end ofthese policies, they are also held most accountable for any failures ineffective implementation. The systemic factors, including: differences inlocal and regional institutions; the organizations that make decisions aroundfunctions, accountability and resource allocation; and the immediateenvironments surrounding the schools, are often ignored. Urbanization and its allied processes have made aprofound impact on the environment of the metropolitan cities of India. Inorder to mitigate the adverse effects of urbanization on environment in citiesand to strengthen their governance, applying the local approach becameessential. An important initiative of the Government of India to strengthenmunicipal governance is the enactment of the Constitutional (74th Amendment)Act (CAA) in 1992.